Performances evaluation of four typical unmanned aerial vehicles used for pesticide application in China - Shilin, Wang; Jianli, Song; Xiongkui, He; Le, Song; Xiaonan, Wang; Changling, Wang; Zhichong, Wang; Yun, Ling (International Journal of Agricultural and Biological Engineering, 2017)
In recent years, unmanned aerial vehicles (UAVs) for plant protection have achieved rapid development in China. In order to test and evaluate the performances of pesticides application and development status of UAVs in China, four typical UAV models were selected to test the spraying coverage, penetrability, droplets density and the work efficiency. The results showed that the deposition and spraying liquid coverage were inconsistent both in lateral and longitudinal direction. Under the condition of the similar amount of spray volume and operation parameters, the volume median diameter (VMD) of the droplet was negatively correlated with the coverage density. The failure of the UAVs for plant protection mainly took up on the blockage of nozzle, transfusion tube and the liquid pump. The failure rate of UAVs took up 3.73%-4.36% of the total working time. The operation of UAVs during ground service took up 50% of the total working time, the preparation work took up 10%, and the route planning took up around 10%, while net operation time only took up around 30%. On the whole, the high efficiency of UAV was not fully achieved; the daily operated area was not in a satisfactory level now. The spraying performances of UAVs still need further improvement. Keywords: unmanned aerial vehicle, work efficiency, pesticide application, deposition, distribution DOI: 10. 25165/j.ijabe.20171004.3219 Citation: Wang S L, Song J L, He X K, Song L, Wang X N, Wang C L, et al. Performances evaluation of four typical unmanned aerial vehicles used for pesticide application in China. Int J Agric & Biol Eng, 2017; 10(4): 22–31.